Digenean Trematodes from Tetraodontiform Fishes from Japanese and Adjacent Waters - Machida, M.; Kuramochi, T. (Bulletin of the National Science Museum. Series A, Zoology, 1999)
Twenty-eight species of digeneans are recorded from tetraodontiform fishes of Japanese and adjacent waters. Five new species and two new genera are named : Sacculoacetabulum ohjibah gen. & sp. nov. (Zoogonidae), Deretrema (Spinoderetrema) triodontis sp. nov. (Zoogonidae) and Neomegacreadium okinawanum gen. & sp. nov. (Schistorchiidae) from Triodon macropterus; Lobatocreadium magnum sp. nov. (Lepocreadiidae) from Ostracion cubicus. Sacculoacetabulum is characterized by a balloon-shaped acetabulum, the orifice of which is narrow, located at the midanterior edge and surrounded by powerful muscular sphincter. Neomegacreadium is distinguished from the related Megacreadium by having a mouth enclosed by a broad muscular lobe anteriorly and muscular bundle lateroposteriorly, a uroproct, ten or occasionally 11 or 12 testes, vitellaria extending to the posterior level of the oral sucker. The following taxonomic changes are proposed : Maculifer chilomycteri Yamaguti, 1959 is synonymous with Heterolebes maculosus Ozaki, 1935; Aponurus vitellograndis Layman, 1930 and A. rhinoplagusiae Yamaguti, 1934 are synonymous with A. laguncula Looss, 1907.